2010
DOI: 10.1128/iai.00862-09
|View full text |Cite
|
Sign up to set email alerts
|

Stressor Exposure Disrupts Commensal Microbial Populations in the Intestines and Leads to Increased Colonization by Citrobacter rodentium

Abstract: The gastrointestinal tract is colonized by an enormous array of microbes that are known to have many beneficial effects on the host. Previous studies have indicated that stressor exposure can disrupt the stability of the intestinal microbiota, but the extent of these changes, as well as the effects on enteric infection, has not been well characterized. In order to examine the ability of stressors to induce changes in the gut microbiota, we exposed mice to a prolonged restraint stressor and then characterized m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
309
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(327 citation statements)
references
References 53 publications
15
309
3
Order By: Relevance
“…A very recent report may shed some light into this question. Work from Bailey et al (2010) demonstrated that such stressinduced changes can indeed alter the microbial diversity of the gut to such a degree that provides a greater opportunity for a pathogen to infect a host. Bailey et al stressed mice and showed through the use of a metagenomics-based 454 pyrosequencing techniqure that the microbial diversity of the colon was altered to such a degree as to provide a more favourable environment for infection with the gut pathogen Citrobacter rodentium.…”
Section: Microbial Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent report may shed some light into this question. Work from Bailey et al (2010) demonstrated that such stressinduced changes can indeed alter the microbial diversity of the gut to such a degree that provides a greater opportunity for a pathogen to infect a host. Bailey et al stressed mice and showed through the use of a metagenomics-based 454 pyrosequencing techniqure that the microbial diversity of the colon was altered to such a degree as to provide a more favourable environment for infection with the gut pathogen Citrobacter rodentium.…”
Section: Microbial Endocrinologymentioning
confidence: 99%
“…Bailey et al stressed mice and showed through the use of a metagenomics-based 454 pyrosequencing techniqure that the microbial diversity of the colon was altered to such a degree as to provide a more favourable environment for infection with the gut pathogen Citrobacter rodentium. Critically, Bailey et al showed that these changes in microbiota occurred in the absence of any demonstrable change in a number of immune-related parameters (Bailey et al, 2010).…”
Section: Microbial Endocrinologymentioning
confidence: 99%
“…After resolving based upon these parameters, the percentage of each fungal ID was individually analyzed for each sample providing relative abundance information within and among the individual samples based upon relative numbers of reads within each. Evaluations presented at each taxonomic level, including percentage compilations, represent all sequences resolved to their primary identification or their closest relative (Bailey et al, 2010).…”
Section: Fungal Identificationmentioning
confidence: 99%
“…Database sequences were characterized as high quality based upon similar criteria utilized by RDP ver 9 (Cole et al, 2009). Using a .NET and C# analysis pipeline, the resulting BLASTn outputs were compiled and were validated using taxonomic distance methods, and data reduction analysis was performed as described previously (Bailey et al, 2010).…”
Section: Fungi Diversity Data Analysismentioning
confidence: 99%
See 1 more Smart Citation